2017
DOI: 10.1007/s12544-017-0258-4
|View full text |Cite
|
Sign up to set email alerts
|

Opening the door to social equity: local and participatory approaches to transportation planning in Montreal

Abstract: Purpose Transportation systems play a key role in providing individuals with a diversity of means to access their desired destinations and have significant impacts on their quality of life. The social perspective of mobility is, however, marginalized in the current model of transportation planning and significant changes are called for. This study aims to identify the barriers and opportunities of local participatory approaches to trigger changes in transportation planning in Montreal, drawing on the concept o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…They need immigrants to be mobile and able to move around to improve the integration process. Again, research is confirmed [2,3].…”
Section: Interpretation and Recommendationsmentioning
confidence: 69%
See 2 more Smart Citations
“…They need immigrants to be mobile and able to move around to improve the integration process. Again, research is confirmed [2,3].…”
Section: Interpretation and Recommendationsmentioning
confidence: 69%
“…Mobility is an important component of social participation and integration. It allows access to employment, education, and social networksin total, to modern life and societal opportunities [1][2][3]. Digitalisation can have a substituting effect: Internet and mobile devices allow home office solutions for a number of jobs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our sample of plans nevertheless illuminates practices which, according to previous studies, can raise the voices of socially‐excluded groups in planning procedures and outcomes. The mailing of brochures detailing plan design procedures to all residents (St. John's) and continuous public engagement over two years at a downtown mall storefront (Saint John) demonstrate proactive outreach to communities with poor news or internet access while simultaneously generating public interest in planning objectives and, ultimately, helping planners to glean insights from non‐opinion‐leading constituencies (Elvy ; Boisjoly and Yengoh ). Making its way into the more recent plans, social media facilitates transparent debate among community members about planning issues, particularly benefiting those whose neighbourhood and household circumstances preclude attendance at set‐time, brick‐and‐mortar meetings (Evans‐Cowley and Griffin ).…”
Section: Discussionmentioning
confidence: 99%
“…Other efforts are necessary to gain a more comprehensive understanding of the long-term equity impacts of transport projects in terms of health, travel costs and road safety. Other research questions that deserve careful attention from future studies include the long-term effects of transport investments on real estate values (Jun, 2012;Stokenberga, 2014), gentrification processes (Gaffney, 2016) and issues of governance and participatory decision-making which are also of key importance for the co-production of fair transport policies (Boisjoly & Yengoh, 2017;Fainstein, 2010).…”
Section: Discussionmentioning
confidence: 99%